Machine interference model application in woven fabric production. Issue 4 (3rd April 2021) - Çelikkiran, Sezin; Ünal, Can
Abstract: In today's production control and analysis in the weaving rooms is provided by a system which permits the automatic and immediate collection (in real time) of the data concerning the running of each weaving machine (stop, weft breakage, warp breakage). The result is the availability of objective and complete data which can build the base for the most appropriate choices and interventions aimed at improving the production of the weaving departments. Weaving is a stage where the yarn becomes a surface and it is the most important cost center due to operator density, machine density and energy consumption. In this study, an application is made on the machine interference problem on weaving plant in a factory producing woolen fabric. Further, a study has been conducted on how the number of operators allocated in order to eliminate these downtimes will provide optimum conditions. For this study, three of the most produced fabrics in the facility are selected and data on the loom group where these fabrics were produced are collected. The optimum number of machines that an operator should be serviced has been examined according to this collected data and production costs by using queuing theorem.